Hypermineralization in the femoral neck of the elderly. (15th April 2019) - Tang, Tengteng; Wagermaier, Wolfgang; Schuetz, Roman; Wang, Qiong; Eltit, Felipe; Fratzl, Peter; Wang, Rizhi
Graphical abstract: Abstract: Hip fragility depends on the decline in bone mass as well as changes in bone microstructure and the properties of bone mineral and organic matrix. Although it is well-established that low bone mass or osteoporosis is a key factor in hip fracture risk, it is striking to observe that 92% of 24 patients who have sustained an intracapsular hip fracture showed hypermineralization at the superior-anterior quadrant, a critical region associated with increased hip fracture risk. In-depth material studies on a total of 12 human cadaver femurs revealed increased degree of mineralization in the hypermineralized tissue: calcium weight percentage as measured by quantitative backscattered electron imaging increased by approximately 15% compared with lamellar bone; mineral-to-matrix ratio obtained by Raman microspectroscopy imaging also increased. Immunohistochemistry revealed localized type II collagen in the hypermineralized region, implying its cartilaginous nature. At the ultrastructural level, X-ray scattering revealed significantly smaller (on average 2.3 nm thick and 15.6 nm long) and less ordered bone minerals in the hypermineralized tissue. Finally, the hypermineralized tissue was more brittle than lamellar bone under hydrated state – cracks propagated easily in the hypermineralized region but stopped at the lamellar boundary. This study demonstrates that hypermineralization of femoral neck cortical bone is a source of bone fragility which is worth considering in future fracture risk assessment when the origin of hip fracture is unclear based on current evaluation standards. Statement of Significance: Hypermineralization of femoral cortical bone in older adults might occur in many more hip fracture cases than presently known. Yet, this tissue remains largely unknown to the orthopedic community possibly due to coarse resolution of clinical imaging. The current study showed the hypermineralized tissue had reduced fracture resistance which could be attributed to the material changes in mineral content, organic matrix, and mineral platelets properties. It thus could be a source for fracture initiation. Consequently, we believe hypermineralization of femoral neck cortical bone should be considered in hip fragility assessment, especially when low bone mass cannot be identified as a primary contributor to hip fracture.